A systematic review of internet-delivered cognitive behavior therapy for alcohol misuse: study characteristics, program content and outcomes. Issue 4 (3rd July 2020) - Hadjistavropoulos, Heather D.; Mehta, Swati; Wilhelms, Andrew; Keough, Matthew T.; Sundström, Christopher
ABSTRACT: Alcohol misuse is a common, disabling and costly issue worldwide. Internet-delivered cognitive behavior therapy (ICBT) has the potential to reduce the harms of alcohol misuse, particularly for individuals who are unable or unwilling to access face-to-face therapy. A systematic review was conducted using Medline, CINAHL, EMBASE and PsycINFO databases for all relevant articles published from 1980 to January 2019. Randomized controlled trials (RCTs) were included if (i) an ICBT intervention targeting alcohol misuse was delivered; (ii) participants were aged 18 years or older; and (iii) primary outcomes were quantity of drinking. A qualitative analysis was conducted on the content of the ICBT programs. Fourteen studies met inclusion criteria. Most studies included participants from the general population, while studies conducted within clinic settings with diagnosed individuals were rare. The programs were similar in terms of included modules. Small effects were seen in studies on self-guided ICBT, while therapist-guided ICBT rendered small to large effects. The current review indicates that ICBT has a significant effect in reducing alcohol consumption. Larger studies evaluating ICBT compared to active control groups especially within clinic settings are warranted.